Digital Currencies: Conceptualization of Risks and Regulatory Opportunities - V. V. Maslennikov; A. V. Larionov (Мир новой экономики, 2022)
The subject of the study is the risks of the development of digital currencies. The study suggests that when solving the existing technological problems of creating a digital currency, Suppose we are talking about digital currencies not controlled by the state and the central bank. The study suggests that after solving the existing technological problems concerning the creation of digital currency, a reorientation of the national entities can occur to make payments in digital currencies to anonymize payments, avoid taxes, and reduce the costs associated with the transfer. As a result, the capabilities of national state bodies in regulating the economic activities of economic entities may decrease. The share of their shadow interaction may also increase. Problems in the performance of the fiscal function of the state may become more acute. The purpose of this research is to conceptualize the risks of the emergence and regulation of the use of supranational digital currencies as a means of payment. The moving of national cash flows to the supranational level – to the sphere of digital currency exchange will negatively affect the completeness of filling the state budget and its ability to perform basic functions. This process will create a real threat to economic security. The study reveals aspects of the development of the digital ruble and the possibility of reducing the risks of using digital currencies by creating new mechanisms for state regulation of economic entities. The research examines the prospects for reducing the attractiveness of supranational digital currencies.